Categorization of English learners and teachers styles and pedagogical suggestions to improve English teaching environment at Mekong University = - Phạm, Thị Phương Dung (Trường Đại học Cần Thơ, 2009)
This thesis was implemented aiming at finding out favored learning and teaching styles of English learners and teachers at Mekong University; teachers awareness of their learners learning styles and their own teaching styles; learners awareness of their learning styles; difference between learning styles of male and female learners and whether there was a mismatch between learning styles and teaching styles.